2015
DOI: 10.4088/pcc.13m01551
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Insomnia Symptoms as Risk Factors for Suicidal Ideation in a Nationally Representative Sample

Abstract: Abnormalities of sleep duration and continuity should prompt a clinical assessment for suicide risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 58 publications
1
26
0
1
Order By: Relevance
“…Sleep duration has also been identified as a suicide risk factor. 102 In the general population, overall mental health has been identified as the leading predictor of self-reported insufficient sleep. 30 …”
Section: Sleep Effects On Health and Longevitymentioning
confidence: 99%
“…Sleep duration has also been identified as a suicide risk factor. 102 In the general population, overall mental health has been identified as the leading predictor of self-reported insufficient sleep. 30 …”
Section: Sleep Effects On Health and Longevitymentioning
confidence: 99%
“…However, across numerous studies, associations between insomnia symptoms and suicide-related variables have been independent of depressive symptoms and/or other potential confounders (ie, age, sex, fatigue, chronic health problems, anhedonia, hopelessness, anxiety symptoms, substance use, cognitive ability, or the presence of any psychiatric illness). 19 , 23 , 25 , 30 , 31 , 33 , 34 , 40 , 42 , 46 , 48 , 51 , 57 , 61 , 64 , 66 , 68 , 69 , 72 74 …”
Section: Insomnia Symptomsmentioning
confidence: 99%
“…Additional inconsistencies include the risk conferred by specific insomnia symptoms (see Table 2 ). Research does not show a clear pattern regarding whether onset, maintenance, or terminal insomnia independently heighten suicide risk, with several studies showing that concurrently reporting two of these three insomnia symptoms may confer greater risk for suicide ideation 40 , 42 , 46 , 57 and attempts, 30 , 31 , 75 , 76 intent to attempt suicide, 72 and death by suicide. 66 This suggests that greater risk may result from the presence of multiple sleep disturbances.…”
Section: Insomnia Symptomsmentioning
confidence: 99%
“…Findings are mixed, though, on whether depression affects this association. At least one study found that short sleep duration was associated with suicidal ideation independent of depression in adults (21), whereas other studies found that depression better explains the association between sleep duration and suicidality (22,23). Among individuals who have suicidal ideation, shorter sleep duration, and poorer sleep quality predicted next day increases in suicidal ideation even when adjusting for depression severity.…”
Section: Introductionmentioning
confidence: 99%
“…Among individuals who have suicidal ideation, shorter sleep duration, and poorer sleep quality predicted next day increases in suicidal ideation even when adjusting for depression severity. Some researchers have proposed that short or long sleep duration may interact with insomnia, such that the two combined result in greater suicidality (22,24).…”
Section: Introductionmentioning
confidence: 99%